2009
DOI: 10.1038/nm.2019
|View full text |Cite
|
Sign up to set email alerts
|

Arrested maturation of excitatory synapses in autosomal dominant lateral temporal lobe epilepsy

Abstract: A subset of central glutamatergic synapses are coordinatelypruned and matured by unresolved mechanisms during early postnatal life. We report that human epilepsy gene LGI1, mutated in autosomal dominant lateral temporal lobe epilepsy (ADLTE), mediates this process in hippocampus. We introduced full-length genes encoding (1) ADLTE truncated mutant LGI1 (835delC) and (2) excess wild-type LGI1 proteins into transgenic mice. We discovered that the normal postnatal Kv1 channel-dependent down-regulation of presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
192
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(212 citation statements)
references
References 43 publications
12
192
3
3
Order By: Relevance
“…However, inhibitory synaptic transmission is not affected in LGI1 mutant mice (7,13) and conditional LGI1 knock out in inhibitory parvalbumin interneurons does not confer an epileptic phenotype (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inhibitory synaptic transmission is not affected in LGI1 mutant mice (7,13) and conditional LGI1 knock out in inhibitory parvalbumin interneurons does not confer an epileptic phenotype (8).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of glutamatergic neurotransmission in hippocampal slices from Lgi1 −/− mice has yielded conflicting reports. Furthermore LGI1 has been implicated in neural development, and perturbed maturation may thus contribute to the epileptic phenotype (11)(12)(13).…”
mentioning
confidence: 99%
“…Another proteomic study identified the transmembrane proteins ADAM22 and ADAM23 as LGI1 receptors and suggested that LGI1 modulates synaptic function by stabilizing levels of cell surface AMPA receptors (Fukata et al, 2006). More recently, Zhou et al (2009) reported that LGI1 plays a role in the pruning and maturation of excitatory synapses in the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the roles of LGI1 in synaptic transmission, an alternative hypothesis that LGI1 regulates neuronal development was proposed by analyzing transgenic mice carrying the human ADPEAF mutation 835delC, which truncates the C-terminal EPTP domain of LGI1 (10). Thus, the physiological function of LGI1 in the brain remains controversial.…”
mentioning
confidence: 99%